Taxarea tranzacţiilor financiare şi consecinţele sale asupra creşterii economice, stabilităţii financiare şi finanţelor publice; Taxing financial transactions and its consequences on economic growth, financial stability and public finances - Bogdan Moinescu; Bogdan Dumitrescu; Iustina Boitan (European Institute of Romania, 2013)
– The severity of the global financial crisis has highlighted major structural limits not only at the level of credit institutions' risk management strategies, but also in the financial safety net. There were very few rules at the onset of the international financial crisis, to determine the actions to be taken by the authorities in case of distressed banks. Lender of last resort funding by central banks, deposit guarantee schemes and the prudential regulatory framework, as they were before the crisis, failed to stem the propagation of systemic shock that spread to the entire European banking system, after the collapse of Lehman Brothers, in the mid-September 2008. The newly created situation showed that public authorities do not have adequate means to handle the situation of distressed banks on today's globalized markets. When a bank had been under stress, there was the risk of contaminating other financial institutions, including those beyond the borders of a country. During the systemic events, several major banks were in such a situation (Fortis, Lehman Brothers, Icelandic banks, Anglo Irish Bank, Dexia), which indicated that existing mechanisms were not effective, being necessary the design of additional elements, in order to allow a proper management of distressed financial institutions. [...]
Keywords: 330; Finanztransaktionssteuer; Wirkungsanalyse; Wirtschaftswachstum; Öffentliche Finanzen